Efficient extraction of refractory Cr from stainless steel dust by sodium persulfate oxidation roasting - Jun Li; Menglan Wu; Zhen Wu; Weizhen Liu; Zhang Lin; Xiaoqin Li (Waste Management, 2024)

Novel method for reducing NDMA formation from daminozide during ozonation: Performances and mechanisms - Linfang Li; Qing Lin; Xiaobin Liao; Tianze Liu; Huan Qi; Qingsong Li; Menglan Gao; Jing Zou; Zhenming Zhou; Mingzhi Huang; Zhimin Yang (Journal of Cleaner Production, 2024)

Critical review for the potential analysis of material utilization from inorganic industrial solid waste - Xuan Guo; Menglan Zeng; Hongdi Yu; Fawei Lin; Jingwei Li; Wenlong Wang; Guanyi Chen (Journal of Cleaner Production, 2024)

Pyrolysis/combustion potential and heavy metal risk of oily sludge and derived products in industrial scale - Hongdi Yu; Jiantao Li; Fawei Lin; Menglan Zeng; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2023)

Exploring Br-’s roles on non-brominated NDMA formation during ozonation: Reactive oxygen species contribution and brominated intermediate path validation - Menglan Gao; Xiaobin Liao; Jing Yu; Xinna Lin; Huan Qi; Linlu Shen; Shupo Liu; Zhimin Yang (Journal of Hazardous Materials, 2023)

Chitin synthase is involved in vegetative growth, asexual reproduction and pathogenesis of Phytophthora capsici and Phytophthora sojae - Wei Cheng; Menglan Lin; Min Qiu; Liang Kong; Yuanpeng Xu; Yaning Li; Yan Wang; Wenwu Ye; Suomeng Dong; Shuilin He; Yuanchao Wang (Environmental Microbiology, 2019)
Summary Chitin is a structural and functional component of the fungal cell wall and also serves as a pathogen‐associated molecular pattern (PAMP) that triggers the innate immune responses of host plants. However, no or very little chitin is found in the fungus‐like oomycetes. In Phytophthora spp., the presence of chitin has not been demonstrated so far, although putative chitin synthase (CHS) genes, which encode the enzymes that synthesize chitin, are present in their genomes. Here, we revealed that chitin is present in the zoospores and released sporangia of Phytophthora , and this is most consistent with the transcriptional pattern of PcCHS in Phytophthora capsici and PsCHS1 in Phytophthora sojae . Disruption of the CHS genes indicated that PcCHS and PsCHS1 , but not PsCHS2 (which exhibited very weak transcription), have similar functions involved in mycelial growth, sporangial production, zoospore release and the pathogenesis of P. capsici and P. sojae . We also suggest that chitin in the zoospores of P. capsici can act as a PAMP that is recognized by the chitin receptors AtLYK5 or AtCERK1 of Arabidopsis . These results provide new insights into the biological significance of chitin and CHSs in Phytophthora and help with the identification of potential targets for disease control.

Assessment of formaldehyde levels in relation to respiratory and allergic symptoms in children from Alba County schools, Romania - Iulia A. Neamtiu; Shao Lin; Menglan Chen; Carmen Roba; Eva Csobod; Eugen S. Gurzau (Environmental Monitoring and Assessment, 2019)